2017
DOI: 10.1177/0394632017749356
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin: A potential biomarker of PJI? A comparative analysis with known and new infection biomarkers

Abstract: There is still no "gold standard" for the diagnosis and prognosis of post-operative periprosthetic joint infection (PJI). Among serum biomarkers, an emerging molecule is presepsin, the soluble fraction of CD14, recently described in other settings as a powerful diagnostic tool to detect sepsis at different degrees of severity. The aim of this study was to investigate the diagnostic and prognostic value of presepsin in PJI. A total of 30 patients with PJI and 30 patients without PJI were enrolled. Presepsin, C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Many novel serum and synovial biomarkers, such as CD14, TREM-1, and TLR2, have shown potential in the diagnosis of PJI. 8 However, marker detection techniques are not readily available in many hospitals, and conflicts exist between different studies, making the test results difficult to interpret. It is interesting to note these cytokines are upstream of the inflammatory pathway, and will eventually trigger the expression of the cytokine interleukin-6 (IL-6) under septic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many novel serum and synovial biomarkers, such as CD14, TREM-1, and TLR2, have shown potential in the diagnosis of PJI. 8 However, marker detection techniques are not readily available in many hospitals, and conflicts exist between different studies, making the test results difficult to interpret. It is interesting to note these cytokines are upstream of the inflammatory pathway, and will eventually trigger the expression of the cytokine interleukin-6 (IL-6) under septic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that presepsin has the potential to be a new biomarker of septic arthritis. At the same time, Marazzi et al 29 examined this marker in patients with PJI and demonstrated its higher diagnostic value compared with CRP and IL-6. However, in our study, when comparing presepsin with HNP1-3, no statistically significant correlation was demonstrated in either serum or synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…This data is in contrast to prior published data of several different surgical disciplines: Marazzi et al assessed Presepsin as a potential biomarker for periprostetic joint infection in a cohort of 30 patients with periprostetic joint infection compared to 30 without. In their series, Presepsin showed greater diagnostic value as assessed by ROC-AUC than established markers for postoperative infections such as CRP or IL-6, namely AUC 0.926 compared to AUC 0.750 and AUC 0.821 [ 27 ]. Also in cardiac surgery patients, Presepsin has shown a comparable predictive value for major adverse events as procalcitonin and even a better predictive value for in-hospital and 6-months mortality [ 28 ].…”
Section: Discussionmentioning
confidence: 99%